Co2O3 substitution effects on the structure and microwave dielectric properties of low-firing (Zn0.9Mg0.1)TiO3 ceramics. Issue 5 (1st April 2018) - Yang, Hongyu; Li, Enzhu; Yang, Yingfeng; Shi, Yan; He, Hongcai; Zhang, Shuren
Abstract: Low-firing (Zn0.9 Mg0.1 )1−x Cox TiO3 (x = 0.02–0.10) (ZMCx T) microwave dielectric ceramics with high temperature stability were synthesized via conventional solid-state reaction. The influences of Co2 O3 substitution on the phase composition, microstructure and microwave dielectric properties of ZMCx T ceramics were discussed. Rietveld refinement results show the coexistence of ZnTiO3 and ZnB2 O4 phases at x = 0.02–0.10. (Zn0.9 Mg0.1 )1−x Cox TiO3 ceramic with x = 0.06 (ZMC0.06 T) obtains the best combination microwave dielectric properties of: ε r = 21.58, Q × f = 53, 948 GHz, τ f = − 54.38 ppm/°C. For expanding its application in LTCC field, 3 wt% ZnO-B2 O3 -SiO2 (ZBS) and 9 wt% TiO2 was added into ZMC0.06 T ceramic, great microwave dielectric properties were achieved at 900 °C for 4 h: ε r = 26.03, Q × f = 34, 830 GHz, τ f = − 4 ppm/°C, making the composite ceramic a promising candidate for LTCC industry.